Race and the Making of the Mormon People. - Mueller, Max Perry (The University of North Carolina Press, 2017)
"Max Perry Mueller argues that the nineteenth-century history of the Church of Jesus Christ of Latter-day Saints illuminates the role that religion played in the formation of the notion of the three 'original' American races--'red, ' 'black, ' and 'white'--for both Mormons and others in the Intermountain West. Notably recovering the voices of a handful of black and Native American Mormons who persistently wrote themselves into the Mormon archive, Mueller threads together historical experience and scriptural hermeneutics, finding that the Book of Mormon is key to understanding how early Mormons both departed from and reflected antebellum conceptions of race as biblically and biologically predetermined. Mormon thought both challenged and reaffirmed the essentialist nature of the racialized American experience"--
Cover; Title; Copyright; Dedication; Contents; Figures; Acknowledgments; Prologue. Visions; Introduction. Race on the Page, Race on the Body; 1 The Book of Mormon: A (White) Universal Gospel; 2 Marketing the Book of Mormon to Noah's Three Sons; 3 From Gentile to Israelite; 4 "Aunt Jane" or Joseph's Adopted Daughter?; 5 People Building, on Bodies; 6 People Building, on Paper; Epilogue. Performing Red, Black, and White American; Notes; Bibliography; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; V; W; Y; Z.
Print version record.
Master record variable field(s) change: 050
Keywords: Church of Jesus Christ of Latter-day Saints -- History; Book of Mormon; Mormons -- West (U.S.); Mormon Church -- Membership; Race relations -- Religious aspects -- Mormon Church; Race -- Religious aspects -- Mormon Church; Mormon Church -- History; RELIGION -- Christianity -- Denominations; HISTORY -- United States -- 19th Century; Electronic books